Pareto Distribution in Non-Proportional Reinsuranc - Pacáková, Viera (Zastosowanie modelu pareto w reasekuracji, 2010)
In this paper we use the Pareto model to estimate risk premium for excess of loss treaties with high deductibles, where loss experience is insufficient and could therefore be misleading. Pareto distribution is possible use to estimate the unknown frequency of losses exceeding any given high deductible if we know the frequency at a low deductible. Having learnt how to extrapolate frequencies and to determine expected excess losses, we can calculate the expected excess loss burden, or the risk premium. If the risk premium for one layer of an excess of loss programme is known, it becomes possible to extrapolate risk premiums directly for additional layers.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 117, s. 216-322